Mejoramiento de las propiedades Microestructurales, Físicas y Mecánicas de Matrices Poliméricas - Viviano Agreda, Elmer Walter (2019)
In front of the environmental problems originated by the excessive use of plastics the oil-based products, the biopolymers rise like a sustainable alternative. However, your properties physical mechanics and water barriers are deficient, which is why such like the chemical modification of starch, addition of materials of reinforcement and mixture of biodegradable polymers have studied improving methods themselves. The chemical modifications of bigger impact are esterification, oxidation and etherification or hidroxipropilation. Inside the materials of reinforcement more used they are additives and agents of nucleation, natural fibers and nanorefuerzos inside of the ones that they have the nanoarcillas and nanocelluloses. In relation to the mixtures polymeric starch, the granular starch, copolymers compounds of graft of starch, starch the thermoplastic and foams of starch expanded have set for themselves as an emerging alternative. The following revision sought to compile grounds and works accomplished in this item princiapal with chemical modifications of starch.